2018
DOI: 10.21470/1678-9741-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Preoperative Vitamin D Supplementation on Postoperative Atrial Fibrillation

Abstract: ObjectiveTo assess the relationship between preoperative vitamin D (vitD) supplementation and the development of postoperative atrial fibrillation (POAF).MethodsThe study group consisted of 328 consecutive patients. The ınfluence of preoperative vitD supplementation on POAF was reviewed in 136 patients who underwent coronary artery bypass graft surgery with vitD insufficiency (n=80) and vitD deficiency (n=56). Patients were assigned to receive either oral vitD (50.000 U) (treatment group, n=68) or not (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Cerit et al Investigated the effects of preoperative vitamin D supplementation on postoperative AF development. According to this study, vitamin D has no impact on preventing postoperative AF in patients with insufficiency, but it helps to reduce postoperative AF in patients with a deficiency 22 .…”
Section: Discussionmentioning
confidence: 83%
“…Cerit et al Investigated the effects of preoperative vitamin D supplementation on postoperative AF development. According to this study, vitamin D has no impact on preventing postoperative AF in patients with insufficiency, but it helps to reduce postoperative AF in patients with a deficiency 22 .…”
Section: Discussionmentioning
confidence: 83%
“…Despite identification of important risk factors for AF, such as old age, arterial hypertension, HF, CAD, valvular heart disease, surgery, and hyperthyroidism, a significant fraction of its risk remains currently unexplained [ 71 ]. Recent studies showed that low vitamin D levels are associated with AF and may be implicated in its pathogenesis, thus suggesting the potential of vitamin D to also become a therapeutic target in this clinical setting [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Vitamin D and Atrial Fibrillationmentioning
confidence: 99%
“…Oxidative stress, inflammation, and RAAS activation are the main mechanisms responsible for atrial fibrosis and might be associated with AF recurrence after ablation in patients with vitD deficiency [21] . Additionally, preoperative vitD supplementation could prevent postoperative AF after coronary artery bypass surgery [22] .…”
Section: Discussionmentioning
confidence: 99%